Meaning Making and (re)positioning in the life trajectory of women with endometriosis in Brazil - Furtado, Clara Baltar Freire; Ferreira, Ligia Ribeiro; Aléssio, Renata Lira dos Santos (Psicologia e Saber Social, 2024)
The aim of this article was to analyze the meanings and (re)positionings of Brazilian women with endometriosis in their developmental trajectories. From a social interactionist perspective of human development, we used Positioning Theory as a basis for understanding processes of constitution of the self. Semi-structured interviews were conducted with six cisgender Brazilian women, aged between 22 and 46, who had been diagnosed with endometriosis. A positioning analysis was carried out based on the dimensions called self-self, self-other and self-dominant discourse. Different processes of (re)positioning were observed. In the self-self dimension, the presence of strong symptoms triggered a positioning of differentiation from other women. When others questioned the presence of symptoms, it promoted a feeling of loneliness, generating distance from other people in the self-other dimension. With the arrival of the diagnosis, some of the participants reported greater social recognition and more security in their relationships, as well as greater investment in self-care. Regarding the dominant discourse, social expectations attributed to women were reproduced and renegotiated, as well as repositioning in the face of medical authority. We emphasize the importance of focusing on women’s narratives in order to sensitize health professionals to women’s psychological transformations during the diagnosis and treatment of endometriosis.